Rapid methods for radionuclide contaminant transport in nuclear fuel cycle simulation. (December 2017) - Huff, Kathryn
Highlights: Cyder is a software library for modeling generic-geology spent nuclear fuel disposal in a nuclear fuel cycle simulator. Mathematical models of hydrologic contaminant transport were implemented in Cyder. This suite of mathematical models is appropriate for capturing a broad range of repository concepts. Cyder performance within the Cyclus fuel cycle simulator is demonstrated on timescales appropriate for fuel cycle simulation. Agreement of essential physics is demonstrated between Cyder and a more detailed stand-alone repository performance model. Abstract: Nuclear fuel cycle and nuclear waste disposal decisions are technologically coupled. However, current nuclear fuel cycle simulators lack dynamic repository performance analysis due to the computational burden of high-fidelity hydrolgic contaminant transport models. TheCyder disposal environment and repository module was developed to fill this gap. It implements medium-fidelity hydrologic radionuclide transport models to support assessment appropriate for fuel cycle simulation in theCyclus fuel cycle simulator. Rapid modeling of hundreds of discrete waste packages in a geologic environment is enabled within this module by a suite of four closed form models for advective, dispersive, coupled, and idealized contaminant transport: a Degradation Rate model, a Mixed Cell model, a Lumped Parameter model, and a 1-D Permeable Porous Medium model. A summary of theCyder module, its timestepping algorithm, and the mathematical models implemented within it are presented. Additionally, parametric demonstrations simulations performed withCyder are presented and shown to demonstrate functional agreement with parametric simulations conducted in a standalone hydrologic transport model, the Clay Generic Disposal System Model developed by the Used Fuel Disposition Campaign Department of Energy Office of Nuclear Energy.